A bioinorganic view on the potential chemical space of hydroxyphenylpyruvate dioxygenase-like (HPDL) enzymes - Niko S. W. Lindlar; Rolf Stucka; Sophie M. Gutenthaler-Tietze; Jonathan Gutenthaler-Tietze; Jan Senderek; Lena J. Daumann (JBIC Journal of Biological Inorganic Chemistry, 2026)
Genetic analyses have identified biallelic variants in the 4-hydroxyphenylpyruvate dioxygenase-like ( HPDL ) gene as the cause of a neurodegenerative disease that resembles the primary coenzyme Q10 (CoQ10) deficiency syndromes. HPDL is structurally similar to the well-studied 4-hydroxyphenyl pyruvate dioxygenase (HPPD), an iron(II)/α-ketoacid-dependent enzyme. HPPD is known to catalyze the second step in the tyrosine metabolism, the oxidative conversion of 4-hydroxyphenylpyruvate (4-HPP) to homogentisic acid (HGA). Hereditary HPPD deficiencies result in high blood tyrosine levels (tyrosinemia type III), which are associated with neurological symptoms such as mental retardation and ataxia. In 2021, 4-hydroxymandelate (4-HMA) was identified as the long-sought intermediate of the biosynthetic pathway from tyrosine to CoQ10. CoQ10 is an important electron shuttle needed in mitochondria for ATP production. Interestingly, HPDL was shown to be able to catalyze the oxygen-dependent reaction of 4-HPP to 4-HMA. Both 4-HPA and 4-HBz occur in the CoQ10 biosynthetic pathway of mammals. CoQ10 has been suspected to be necessary for correct neuronal function, a link to the neurodegenerative HPDL variants. Here, we present a bioinorganic model that can mimic this potential role of HPDL in the conversion of 4-hydroxyphenylpyruvic acid (4-HPA) to 4-hydroxybenzaldehyde (4-HBz). We used fully synthetic iron(III)-hydroxido and iron(IV)-oxido complexes with a ligand of the pentapyridyl-type to study the interconversion of 4-HPA to 4-HBz from a bioinorganic point of view. We show that while an iron(IV)-oxido species, as it occurs in HPPD, is capable of performing the first reaction step from 4-HPA to 4-HMA, an iron(III)-hydroxido species is capable of the transformation of 4-HMA to 4-HBz.

SACS variants are a relevant cause of autosomal recessive hereditary motor and sensory neuropathy - Katharina Vill; Wolfgang Müller-Felber; Dieter Gläser; Marius Kuhn; Veronika Teusch; Herbert Schreiber; Joachim Weis; Jörg Klepper; Anja Schirmacher; Astrid Blaschek; Manuela Wiessner; Tim M. Strom; et al. (Human Genetics, 2018)